Graph Model for Minimal Distance and Optimal Circulation in Urban Design - Pingkan S Pioh (Sam Ratulangi University, 2012)
GRAPH MODEL FOR MINIMAL DISTANCE AND OPTIMAL CIRCULATION IN URBAN DESIGNABSTRACT Among the important aspects in urban design are minimal distance and optimal circulation of the traffic network which include good access to the places of interests. The main road network is modeled in graph where the important places are represented by vertices and the main roads between them are represented in edges. A graph is called 3-connected if for every pair of vertices, there are three disjoint paths connecting them. Given the vertices and their locations, this paper focuses to make a 3-connected graph with minimal distance connecting them. This model is simulated in a computer program and applied in a current road network of Manado City, North Sulawesi Indonesia to see whether of not the road network in Manado is already optimal or not. Keywords: graph, n-connected, minimal distance, urban design. Â MODEL GRAF UNTUK JARAK MINIMALDAN SIRKULASI OPTIMAL PADA PERANCANGAN KOTA ABSTRAK Diantara aspek penting dalam perancangan kota adalah jarak yang minimal dan sirkulasi yang baik dari lalu lintas termasuk aksesibilitas dari tempat-tempat penting. Perancangan ini dimodelkan dalam bentuk graf yang simpul-simpul mewakili tempat-tempat penting sedangkan sisi-sisi menyajikan jalan-jalan yang menghubungkan tempat-tempat tersebut. Sebuah graf dikatakan terkoneksi-3 jika untuk setiap pasangan simpul, terdapat 3 jalur saling lepas yang menghubungkan kedua simpul itu. Fokus dari paper ini adalah, jika diberikan simpul-simpul bersama lokasinya, membuat graph yang terkoneksi-3 dengan jarak minimal. Model ini diimplementasikan dalam bentuk program komputer dan diterapkan pada jaringan jalan yang ada di Manado, Sulawesi Utara, Indonesia, sekarang untuk menentukan apakah jaringan jalan di Manado sudah optimal atau belum. Kata kunci: Graf, terkoneksi-3, jarak minimal, perancangan kota